Asosiasi Sitophilus oryzae (Col.: Curculionidae) dan Tribolium castaneum (Col.: Tenebrionidae) dalam Beras: Pertumbuhan Populasi dan Kerusakan Beras - F. X. Wagiman; Praba Kusumaningrum SSW; Samsuri Tarmadja (Universitas Gadjah Mada, 1999)
The association of Sitophilus oryzae (Lin.) (Col.: Curculionidae) and Tribolium castaneum (Herbst.) (Col.: Tenebrionidae) in the white rice, IR64 variety, was studied in the laboratory. Objective of the study was to determine the influence of the association upon their population growth and the white rice deterioration. Adults of the two insect-pest species as many as (a) 50 S. oryzae, (b) 50 S. oryzae and 50 T. castaneum, and (c) 50 T. castaneum were cultured on 0.5 kg of the white rice for two months period. The growth rate of the species was assumed to fit exponential pattern. The results showed that the growth rate of S. oryzae population when it was cultured together with T. castaneum was (r=0.0475) significantly lower than it was cultured alone (r=0.0586), on the other hand, the growth rate of T. castaneum (r=0.0366) when it was cultured together with S. oryzae was significantly higher than it was cultured alone (r=0.0288). The presence of T. castaneum might cause an interference competition for S. oryzae, while broken rice as a result of S. oryzae attack might be a good food source for T. castaneum. The combination of attack pf the two beetle species significantly reduced the white rice quantity and quality; it increased the broken rice, water content, and mustiness.